COMMUNICATION OF SECONDARY PARTS OF SPEECH WITH PARENTHESES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article is scientifically based on the syntactic relationship of parenthesis units with complement and determiner. The semantic connection of word-form, phrase, and sentence-in-parent parentheses is substantiated using examples from the work of art.